Prefigurative urban practices - proposing socioeconomic values beyond the market - Mateus, C.; Olival, F. (What makes urban life worth living? (Re)evaluating the value of urban life, 2023)
The urban way of life has been associated with diversity and the opening of opportunities for plural life projects. However, the institutional discourse projects a quite homogeneous perspective of urban life. A life in which commodification dictates, not only the goods people consume and produce, but even social relations themselves. In the last decades of neoliberalism, concepts like development and progress and, more recently, sustainability and resilience are twisted to fit with values of economic growth, capital accumulation and competition. At the core, these values, that now guide, to a great extent, the institutional vision for the future of our cities, reflect a contamination of unmeasurable social values (cooperation, sharing, autonomy) by a quantifiable and homogenizing form of value: profit. However, cities are also made of prefigurative practices that propose the very diversity that urban life is associated with. Authors like Van der Ploeg, Figueiredo, or Halfacree have been analyzing these phenomena in relation to the repeasantization and counter-urbanization movements. Here, we propose an understanding of these practices as proposals for integrating rural values in the urban sphere. With this in mind, we analyze the case of Rizoma, a multi-sectorial cooperative in Lisbon, and the case of Can Batló, a social centre in Barcelona. Our goal is to reflect on how growth and development, based on a different set of values, can defy and point towards an alternative, not only to the neoliberal ideals of “urban life”, but also to the very urban-rural dichotomy.